Cross-Cultural Perspectives on Tourism Development: A Comparative Analysis of Australia and Indonesia - Hera Oktadiana, Ari Prasetyaningrum, Laila Wati, Hajriana Arfah (Journal of Educational Studies, 2026)
This study compares tourism development in Australia and Indonesia to examine how cultural context influences four key dimensions: cultural integration, community participation, sustainability practices, and governance effectiveness. Using a mixed-methods comparative design, the research draws on questionnaire data from tourism stakeholders in both countries, including policymakers, destination managers, community representatives, and practitioners, complemented by semi-structured interviews. Quantitative data were analyzed using descriptive and inferential statistics, while qualitative data were examined thematically. The findings reveal clear cross-cultural differences in tourism development approaches. Indonesia places greater emphasis on cultural integration and community participation, reflecting the prominence of community-based and culturally grounded tourism models. Australia performs more strongly in sustainability practices and governance effectiveness, indicating a more institutionalized and policy-driven framework. The results also show significant positive relationships between cultural values and broader tourism development dimensions, highlighting culture as a key driver of tourism outcomes. Qualitative insights further stress the importance of balancing economic development with cultural preservation and environmental sustainability. This study contributes to cross-cultural tourism research by demonstrating that tourism development remains culturally differentiated despite globalization. It also offers practical implications for policymakers and practitioners by emphasizing the need for culturally responsive and governance-sensitive tourism strategies that support sustainable development.